2017
DOI: 10.1080/13102818.2017.1316214
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the drought stress response ofDREB2andCAT1genes and evaluation of related physiological parameters in some bread wheat cultivars

Abstract: Abiotic stresses such as drought are among the most significant environmental stress causes in economically important crop plants including wheat (Triticum aestivum L.) and improving their yield is a major goal of plant breeding. In this study, we analysed expression of dehydration responsive element binding factor (DREB2), and an important antioxidant enzyme gene CAT1 in flag leaf of three bread wheat cultivars named Kavir, Kalheydari and Shahpasand under drought stress by RT-qPCR. In another section, physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
0
10
0
2
Order By: Relevance
“…Worldwide agricultural production has been limited by several environmental constraints in the form of abiotic stresses, which affects plants growth, metabolism and development (Eftekhari et al, 2017;Muscolo et al, 2014). Water scarcity is currently one of the most severe limitations of plant development and production (Eftekhari et al, 2017;Jain and Saxena, 2016). The predicted temperature increase and rainfall decrease will be responsible for more frequent drought periods, mainly in the Mediterranean region including the Iberian Peninsula (Kröner et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide agricultural production has been limited by several environmental constraints in the form of abiotic stresses, which affects plants growth, metabolism and development (Eftekhari et al, 2017;Muscolo et al, 2014). Water scarcity is currently one of the most severe limitations of plant development and production (Eftekhari et al, 2017;Jain and Saxena, 2016). The predicted temperature increase and rainfall decrease will be responsible for more frequent drought periods, mainly in the Mediterranean region including the Iberian Peninsula (Kröner et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the sensitive genotypes recorded the lowest means for all studied traits, which may indicate that those genotypes showed a lower capacity to accord with stress conditions. In the same context, (Eftekhari et al 2017;Kamoshita et al 2000;Schonfeld et al 1988) revealed that RWC for tolerant cultivar retain major amount of water than the non-tolerant and RWC reduced significantly under drought stress conditions. Under drought conditions, the decreasing in RWC fundamentally related with the capacity of more tolerant genotypes to better absorb soil, water and to prevent water loss through stomata (Keyvan et al 2010).…”
Section: Discussionmentioning
confidence: 91%
“…DREB2 and DREB2a were also highly expressed in both varieties of Jerusalem artichoke, particularly in QY3, in which the expression of DREB2 was extremely high. It has been proven that DREB2 was closely related to drought stress in wheat [42], A. thaliana [43] and mustard [44]. Compared with the DREB family, which had only a few genes, we identi ed a number of WRKY transcription factors in the Jerusalem artichoke transcriptome data.…”
Section: Transcription Factors and Plant Drought Tolerancementioning
confidence: 99%